Assessment of the possibility of using leucoxene-quartz concentrate as raw material for production of aluminium and magnesium titanates - Evgenii N. Kuzin; Ivan G. Mokrushin; Nataliya E. Kruchinina (Записки Горного института, 2023)
Leucoxene-quartz concentrate is a large-tonnage by-product of development of the Timan oil-titanium field (oil-saturated sandstones) which is not commercially used at present. High content of titanium compounds (to 50 % by weight) and lack of industrial, cost-effective, and safe technologies for its processing determine a high relevance of the work. Conventional processing technologies allow increasing the concentration of TiO2, but they are only a preparation for complex and hazardous selective chlorination. The process of pyrometallurgical conversion of leucoxene-quartz concentrate into aluminium and magnesium titanates was investigated. It was ascertained that the temperature of solid-phase reaction in Al2O3-TiO2-SiO2 system necessary for the synthesis of aluminium titanate (Al2TiO5) is 1,558 °С, and for MgO-TiO2-SiO2 system – 1,372 °С. Scaling up the process made it possible to synthesize a significant number of samples of titanate-containing products, the phase composition of which was studied by X-ray phase analysis. Two main phases were identified in the products: 30 % aluminium/magnesium titanate and 40 % silicon dioxide. In products of pyrometallurgical processing in the presence of aluminium, phases of pseudobrookite (3.5 %) and titanite (0.5 %) were also found. It was ascertained that in magnesium-containing system the formation of three magnesium titanates is possible: MgTiO3 – 25, Mg2TiO4 – 35, MgTi2O5 – 40 %. Experiments on sulphuric acid leaching of samples demonstrated a higher degree of titanium compounds extraction during sulphuric acid processing. An integrated conceptual scheme for processing leucoxene-quartz concentrate to produce a wide range of potential products (coagulants, catalysts, materials for ceramic industry) was proposed.